Study of the influence of models on the drilling temperature of bone measured by thermocouples. (27th April 2020) - You, Fangyi; Li, Jin; Cui, Huzi; Dai, Qiulian
Bone drilling is a standard procedure in medicine mainly for internal fixation with a gripper plate. Drilling bone generates much heat, then the heat causes the temperature of bone to rise, nearby the borehole rapidly, while drilling. Studies indicated that the bone would irreversibly be damaged after being heated up to 47°C for 60 s. Hence, it is vitally important to control the drilling temperature of bone. Two different models of the tibia for drilling simulation were established with ABAQUS software based on finite element analysis in this article. The first model is an approximate ideal model of the tibia with fluid in the bone cavity. And the other one is a tubular tibia without fluid in the bone cavity, and a pair of thermocouples is embedded to match the experimental condition when measuring the drilling temperature. The distribution of heat on the bone and the highest drilling temperature were revealed by simulation, and the influences of drilling parameters on drilling temperature of bone were also explored by variance analysis. The results show that the maximum drilling temperature increases with an increase in the diameter of bit and spindle speed. The drilling temperature also increases as the feed rate increase, but the effect of feed rate on drilling temperature is not as significant as that of spindle speed. The drilling temperatures of two models were obtained by the finite element method. The maximum temperature of model 1 is taken as the benchmark. The temperature of model 2 takes as the experimental result. A formula for modifying the experimental temperature to actual value was derived. Then predicted temperature of model 1 could be achieved to obtain the optimized drilling parameters.